Social care services for patients with HIV at a London teaching hospital; an evaluation. Issue 6 (December 1992) - Bor, R; Elford, J; Murray, D; Salt, H; Tilling, J; Miller, R; Johnson, M
Abstract : OBJECTIVE–To investigate outpatients' use of, and satisfaction with social care services in an HIV unit. DESIGN–Survey of patients with HIV infection using self administered questionnaire. SETTING–Outpatient HIV clinics at the Royal Free Hospital, London, March-April 1991. MAIN OUTCOME MEASURES–Patients' social circumstances, use or intended use of social care services and satisfaction with social care services. RESULTS–The greatest demand was for counselling about coping with HIV (38% of respondents), available medical treatment (24%), counselling for the HIV test (33%), psychological support for emotional (24%) or relationship problems (16%), advice about housing (24%) and financial matters (20%). In general, the use of social care services by men and women was similar. Twice as many men, however, sought help with payment of domestic bills, compared with women. Women were more likely to seek advice about financial benefits, obtaining sterile injecting equipment and discuss sleep and relationship problems. Thirty eight percent of patients were unemployed. Overall, 84% thought the service was good or excellent. Although less than 40% of patients currently used any one service, 60% thought they would use these services in the future. CONCLUSION–The greatest demand for social care services was for coping with HIV, housing and financial matters, and HIV test counselling. More than half the patients stated that they would probably need social care services in future.